Hubungan Envy Terhadap Schadenfreude pada Remaja Putri Fakultas Psikologi UNJANI Angkatan 2019 - Ramadhana, Mochamad Adistya Rizki (LITERATUS, 2024)
Envy and Schadenfreude are two things that we often see in everyday life. This variable is important to discuss because the feelings of inferiority that a person has when comparing themselves with other people can make him feel annoyed with the person who is the source of his envy, which can give rise to satisfaction when the source of his envy fails. This study aims to explore the relationship between envy and schadenfreude among female students of the Faculty of Psychology at UNJANI, class of 2019. Envy and schadenfreude, both commonly observed in daily life, are crucial variables due to their potential to cause feelings of inferiority and subsequent satisfaction when the object of envy experiences failure. The research adopts a correlational design, employing simple random sampling to select 116 respondents from the target population. Data were gathered using scales based on aspects proposed by Ninivaggi (2010) and Richard (2013), with reliability measured using McDonald's coefficient, all exceeding 0.5. Confirmatory Factor Analysis (CFA) was utilized to validate the scales, and Spearman's rank correlation was applied for data analysis. The findings indicate a low but significant positive correlation (r = 0.371, p <.001;>.001) between envy and schadenfreude in the target group. The results suggest that while the majority of respondents exhibit moderate levels of envy, their schadenfreude remains low. The study concludes with implications for further research on the impact of these variables and provides recommendations for future studies.